Predisposition of sciatica in different socioeconomic classes: a brief clinical survey - Aziz, Abdul; Rather, Shameem Ahmad; Bhat, Shabir Ahmad (International Journal Of Community Medicine And Public Health, 2023)
Background: Sciatica became the accepted name for pain radiating from the lower back or buttock into the leg after being distinguished from arthritic hip pain in the 18th century. Several studies suggest strong connection of Socioeconomic status with sciatica. Accurate data on the incidence and prevalence of sciatica is still missing. The objective of this study was to observe a relationship of sciatica patients with their socioeconomic status. Methods: Sixty (60) diagnosed cases of sciatica selected randomly were interrogated and assessed according to the modified Kuppuswamy’s socioeconomic status (SES) scale. Results: It was found that 36.6% were belonging to upper-middle class of society, 35% from lower-middle class, 13.8% from upper-lower class, 8.6% from upper class and only 6.9% were belonging to lower socioeconomic class of society. Conclusions: The current study depicted that the sciatica is more common in middle socioeconomic class followed by upper and lower socioeconomic class respectively.